O ensino de estratégias de leitura na Educação de Jovens e Adultos (EJA): a literatura como proposta para compreensão textual - Guedes, Kilma Cristeane Ferreira (2025)
This study is linked to the line of research named "Literary Readings" of the "Theory, Literature and Critique Concentration Area of the Postgraduate Program in Language Arts-PPGL., from Universidade Federal da Paraiha/UFPB, and to "Teacher training and the relationship between educational practices in reading, literature and literary text assessment Research Group Probeli. This is a doctoral thesis that aims at analyzing how reading strategies taught to high school studens in Young and Adult Education (EJA) can add to text comprehension in literary mediation moments. To that end, a practice was applied to a Cycle VI class (which corresponds to the 3rd year of High School) at Escola Estadual de Ensino Médio and EJA Dostor Otávio Novais, located in the suburbs of the municipality of João Pessoa PB. The qualitative investigation followed a methodological approach to action research. Thus, in the aforementioned practice, the students participated in reading workshops and textual comprehension activities. The theoretical methodological contribution is based on studies conducted by Koch and Elias (2017), Sole (2014), Cosson (2021a, 2021b), Silva (2023), Girotto and Souza (2010). Harvey and Goudvin (2007), among others. Furthermore, in order to investigate the specificities of EJA as teaching modality and its target audience, we revisited the studies conducted by Artoyo (2017), Freire (2001) and others, and related legislation and documents, such as: Lei de Diretrizes e Bases da Educação Nacional (LDH) (Law of Guidelines and Bases of National Eshwarion 9.394/1996, in its 7th edition (Brazil, [1996], 2023) Diretrizes Curriculares Nacionais para a Educação de Jovem e Adultos (National Curricular Guidelines for Youth and Adult Education/ opinion n 11/2000 (Brazil, 2000), and Diretrizes Operacionais para a Educação de Jovem e Adultos (Operational Guidelines for Youth and Adult Education) resolution n° 01/2021 (Brazil, 2021). The practice carried out with the students was analyzed based on observing its stages ("before", "during" and "aller" reading) and the set of activities proposed portfolios highlighted significam contributions from teaching reading strategies applied to literary texts, such as mobilization of previous koowledge by students, establishing connections, inferences, visualizations and questions to construct senses and meanings (both individually and shared) that are appropriate to unknown words or other textual eletnents (theme, setting, characters, problem etc.), preparation of personal summary to facilitated the partial or fiall comprehension of the text, and development of reading skills, particularly those related to the descriptors of the Sistema de Avaliação da Educação Básica (SAEB) (Basic Education Assessmew System). (Brazil, 2001), which are fundamental for textual comprehension and, as sach, for the promotion of a rich literary experience. Thus, the practice contributed both to facilitating textual comprehension by students and encouraging them to practice literary reading, which, in turn, guarantees them the exercise of the right to literature.